STRATEGIES FOR DEVELOPING HAJJ AND UMRAH TRAVEL IN THE PANDEMIC ERA: A STUDY BY DUTARIZKIA TOUR AND TRAVEL IN DEPOK - Fitria, Fitria Destiana (Jurnal Dakwah Tabligh, 2022)
The results of the analysis concluded that Depok and Umrah Tour and Travel applied word-of-mouth strategy as the main strategy, applying geographic segmentation, demographic segmentation, and psychographic segmentation as a mapping strategy; single-focus (niche) marketing targeting strategy; and positioning strategy is “best service”. Mixed with marketing mix theory (1) product: formulating a new product, namely gold savings; (2) price: “at the market”; (3) promotion: actively using social media and maintaining relationships with alumni and partners; (4) distribution: housing and services for implementing employees can be carried out at the office or at home visits. Dutarizkia Tour and Travel formulates to serve products that are useful for prospective pilgrims. This activity is supported by promotions on social media and continuing ongoing relationships with alumni and partners.